2020
DOI: 10.1021/acs.est.0c00712
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Improving Microplastic Removal during Water Treatment: Impact of Coagulation and Flocculation

Abstract: The efficacy of plastic particle removal by municipal water treatment plants is currently uncertain, and the mechanisms involved in microplastic (MP) coagulation and flocculation have only been superficially investigated. The removal of pristine versus weathered plastic debris and the impact of plastic particle size on removal remain largely unexplored. In this study, coagulation, flocculation, and settling performances were investigated using pristine and weathered MPs (polyethylene (PE) and polystyrene (PS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(132 citation statements)
references
References 55 publications
7
125
0
Order By: Relevance
“…The positive effect of coagulant dosing enhancing microplastic particles removal was also confirmed [44]. It was reported that weathered microparticles revealed higher removal efficiency via coagulation and flocculation than fresh particles, due to changes on their surface roughness [45]. Aluminum coagulation is reported to be more efficient and studies on iron coagulation are not as intensively reported as aluminum coagulation.…”
Section: Coagulation/flocculationmentioning
confidence: 64%
“…The positive effect of coagulant dosing enhancing microplastic particles removal was also confirmed [44]. It was reported that weathered microparticles revealed higher removal efficiency via coagulation and flocculation than fresh particles, due to changes on their surface roughness [45]. Aluminum coagulation is reported to be more efficient and studies on iron coagulation are not as intensively reported as aluminum coagulation.…”
Section: Coagulation/flocculationmentioning
confidence: 64%
“…Using a dosage of 1 mL n-butyltrichlorosilane, an almost complete removal could be achieved reaching 98.1%. Studies using aluminum, iron or polyacrylamide based flocculants also showed increased effectivity of higher dosages [13,21].…”
Section: Comparison Of Polymer Typesmentioning
confidence: 98%
“…In comparison Lapointe et al 2020 tested aluminum and polyacrylamide based flocculants towards weathered and unweathered PE and could show that the introduction of polar hydroxyl and carboxylic acid groups by weathering could improve the interaction of the flocculants and microplastics leading to improved removal [21]. This result shows that coagulants with polar sorption sites can lead to enhanced flocculation of polar microplastics.…”
Section: Comparison Of Polymer Typesmentioning
confidence: 99%
See 2 more Smart Citations